Preko Granice - Krelja, Petar (Croatia : Croatian Television ; Croatian Film Club Association, 2008)
On one side of the border lies the small Croatian town Gunja and on the other side Brčko, which has the status of a district in the Republic of Bosnia and Herzegovina. They are connected by a bridge which is used daily, without any special formalities, by people from both sides for their daily business as well as by students. This little town across the border is appealing for many reasons: home supplies and groceries are much cheaper than in Croatia, getting a driver’s license is half the price. A puzzling look at political borders.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films